1991
DOI: 10.1177/001440299105800102
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions of the Regular Education Initiative

Abstract: A survey of 381 special and regular educators assessed perceptions and opinions surrounding the regular education initiative. Confirmatory factor analysis supported an a priori hypothesized structure of teachers' responses. Items factored into 14 categories. These factors describe issues related to preferred placement of students with mild disabilities, teachers' responsibility and ownership, teacher preparedness for meeting the needs of these students, achievement outcomes for all children, and the changes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
3
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(91 citation statements)
references
References 44 publications
5
80
3
2
Order By: Relevance
“…Studies in this area have shown that teachers at the beginning of the implementation feel that they do not have enough time to implement inclusion (Semmel et al, 1991). They are often anxious in terms of pace, learning styles, adaptation of the environment and the amount of time they have to dedicate to children with disabilities.…”
Section: The Role Of Curriculum In Teachers Trainingmentioning
confidence: 99%
“…Studies in this area have shown that teachers at the beginning of the implementation feel that they do not have enough time to implement inclusion (Semmel et al, 1991). They are often anxious in terms of pace, learning styles, adaptation of the environment and the amount of time they have to dedicate to children with disabilities.…”
Section: The Role Of Curriculum In Teachers Trainingmentioning
confidence: 99%
“…• teachers' reluctance to change their culture and teaching practices (Fullan & Miles, 1992), including fears and anxieties associated with change, the practicality of change, perceived school support and personal costs and efforts (Welch, 1989); • the availability of technical assistance (Kauffman, Lloyd & McGee, 1989); • t e a ch e rs' know l e d ge about students' traits, ch a ra c t e ri s t i c s and educational needs (Semmel et al, 1991) Literature on factors that contribute to school quality also suggests that changes in student performance and school quality are related to a set of proximal variables, such as educational strategies and practices, as well as to distal va ri ables, when school re o rga n i s ation and educat i o n a l polices play an important role (Wang, Haertl & Walberg, 1993). According to results that are highlighted in the Wang et al study, the quality of the diagnosis of learn i n g problems could improve if attention were paid to a set of variables that include information about students' capacities and aptitudes; contextual fa c t o rs such as fa m i ly invo l ve m e n t in activities undert a ken at school; and the quality of teacher-student interactions, among others.…”
Section: Factors That Contribute To Academic Achievementmentioning
confidence: 99%
“…• teachers' reluctance to change their culture and teaching practices (Fullan & Miles, 1992), including fears and anxieties associated with change, the practicality of change, perceived school support and personal costs and efforts (Welch, 1989); • the availability of technical assistance (Kauffman, Lloyd & McGee, 1989); • t e a ch e rs' know l e d ge about students' traits, ch a ra c t e ri s t i c s and educational needs (Semmel et al, 1991); • the use of co-operative learning structures ); • the development of working relationships between teachers (Pugach & Johnson, 1994); • c u rricular innovations and new instructional ap p ro a ch e s (Nevin, 1993;Udvari-Solner & Thousand, 1995).…”
Section: Factors That Contribute To Academic Achievementmentioning
confidence: 99%
See 2 more Smart Citations